Faktor risiko konstipasi pada anak - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Dyah Kurniati, M. Juffrie' - Risk factors of constipation in children Background: Despite it is not considered as a dangerous situation in children older than 2 years old, but attention is important in young infant. Improper treatment in constipation may contributed to the raise of anxiety, emotionally disorder either for the children or its relatives. Objective: To determine risk factors related to constipation in children. Design and Methods: A case control study was conducted for all of children who were admitted to ambulatory polyclinic and inpatient clinic of Sardjito Hospital during January 2001 - December 2001. A questionnaire was obtained by the researcher or assistant by direct interview to parent or guardian. Results: We enrolled 86 children, consisted of 43 children in constipation group and the 43 children as control. There was significant difference (p < 0.01) between two groups in the presence of the symptoms (abdominal pain, pain during defecation, vomit, decrease of appetite and encopresis). More children in constipation group and significant difference (p